2022
DOI: 10.1097/md.0000000000029135
|View full text |Cite
|
Sign up to set email alerts
|

The first report on effect of fecal microbiota transplantation as a complementary treatment in a patient with steroid-refractory Cronkhite-Canada syndrome

Abstract: Rationale: Cronkhite-Canada syndrome (CCS) is a rare non-hereditary disease of unknown etiology that is characterized by the appearance of multiple polyps in the entire gastrointestinal (GI) tract, except in the esophagus, with GI and non-GI symptoms. Various factors are associated with the pathogenesis of CCS. Immune dysregulation has been discussed as one of the pathogeneses of CCS, and dysbiosis of the gut microbiota can affect the immune system. Currently, standard treatment has not been established. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“… 1 , 4 In addition, recent reports identified intestinal dysbiosis as one of the risk factors for CCS because the replacement of intestinal bacteria by fecal microbiota transplantation or gut sterilization by antibiotics is effective in CCS. 5 , 6 These findings led us to hypothesize that PSL or TNF‐α‐inhibitors might achieve regression of CCS polyps through suppression of proinflammatory cytokines induced by intestinal dysbiosis. In this study, we provide evidence that regression of CCS polyps by PSL was accompanied by the downregulation of proinflammatory cytokine responses and alterations in intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 1 , 4 In addition, recent reports identified intestinal dysbiosis as one of the risk factors for CCS because the replacement of intestinal bacteria by fecal microbiota transplantation or gut sterilization by antibiotics is effective in CCS. 5 , 6 These findings led us to hypothesize that PSL or TNF‐α‐inhibitors might achieve regression of CCS polyps through suppression of proinflammatory cytokines induced by intestinal dysbiosis. In this study, we provide evidence that regression of CCS polyps by PSL was accompanied by the downregulation of proinflammatory cytokine responses and alterations in intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Furthermore, the effectiveness of the replacement of intestinal microbiota was reported in CCS. 6 Thus, it is likely that proinflammatory cytokine responses triggered by intestinal dysbiosis are involved in the development of CCS and that PSL mediates regression of CCS polyps via suppression of such responses. Notably, intestinal dysbiosis might also accelerate the development of CCS‐associated cancer since the colonization of B. fragilis and P. anaerobius with the promotion of inflammation and oncogenesis is enriched in this case before PSL treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving a sustained endoscopic response is the therapeutic goal and associated with a reduced risk of cancer[ 4 , 25 ]. Kim et al [ 28 ] reported a successful case of fecal microbiota transplantation in the treatment of steroid-refractory CCS. The etiology and pathogenesis of this disease are not yet fully understood, and various other methods are still being explored.…”
Section: Discussionmentioning
confidence: 99%